Effect of Schizochytrium limacinum supplementation to a low fish-meal diet on growth performance, lipid metabolism, apoptosis, autophagy and intestinal histology of Litopenaeus vannamei - Yao, Xinzhou; Lin, Yingying; Shi, Menglin; Chen, Liutong; Qu, Kangyuan; Liu, Yucheng; Tan, Beiping; Xie, Shiwei (Frontiers in Marine Science, 2022)
This experiment aimed to evaluate the effects of the addition of Schizochytrium limacinum to low fish meal diet on growth performance, lipid metabolism, apoptosis, autophagy, and intestinal health of Lipenaeus vanamei. The diet containing 25% fish meal was used as a positive control (FM) and the other three diets contained 15% fish meal and were supplemented with 0, 0.3, and 0.6% S. Limacinum (LF, LFLD, LFHD). The shrimp (0.22 ± 0.00 g) were divided into four replicates of 40 shrimp per tank and fed four times daily to apparent satiation for 8 weeks. The final weight and weight gain rate were significantly higher in shrimp fed the FM and LFHD diets than in shrimp fed LF diet (P<0.05).This experiment aimed to evaluate the effects of the addition of Schizochytrium limacinum to low fish meal diet on growth performance, lipid metabolism, apoptosis, autophagy, and intestinal health of Lipenaeus vanamei. The diet containing 25% fish meal was used as a positive control (FM) and the other three diets contained 15% fish meal and were supplemented with 0, 0.3, and 0.6% S. Limacinum (LF, LFLD, LFHD). The shrimp (0.22 ± 0.00 g) were divided into four replicates of 40 shrimp per tank and fed four times daily to apparent satiation for 8 weeks. The final weight and weight gain rate were significantly higher in shrimp fed the FM and LFHD diets than in shrimp fed LF diet (P<0.05).Hepatopancreas gene expression results showed that the gene expression of 5′ -AMP-activated protein kinase (ampk), acetyl-CoA carboxylase 1 (acc1), malonyl-CoA decarboxylase (mcd) and stearoyl-CoA desaturase (scd1) was significantly higher in shrimp fed the LF diet than those fed the HF diet (P<0.05).Results of genes expression associated with apoptosis in the hepatopancreas showed that the B lymphocytoma-2 (bcl-2), BCL2 associated X apoptosis regulator (bax) and cysteinyl aspartate specific proteinase 8 (caspase 8) genes were significantly lower in shrimp fed the LF diet than those fed the HF diet (P<0.05).